ANALYSIS AND PREDICTION OF GREENFIELD SURFACE SETTLEMENT IN KENNY HILL FORMATION FOR KVMRT - HAZAIRI , HANS (Universiti Teknologi PETRONAS, 2018)
Understanding tunnelling-induced ground movement is an area of great importance for urban tunnelling projects, particularly for risk management. In this paper, observations of ground movement from a case study in the Klang Valley Mass Rapid Transit (KVMRT) Sungai Buloh – Kajang (SBK) Line in Kuala Lumpur are used to identify the governing factors. The KVMRT SBK Line case study presents the back calculation of the soil constant, k, used in fitting surface settlement data to a normal distribution curve. The main findings of this study will be useful as a reference for future tunnelling projects in Kenny Hill Formation.